Progress in green ammonia production as potential carbon-free fuel. (1st September 2021) - Chehade, Ghassan; Dincer, Ibrahim
Highlights: Ammonia production goes green. Small-scale modular ammonia plants are flexible and efficient. The ammonia market is resilient in COVID-19 crises. Abstract: This paper focuses on the challenges, opportunities and future potentials with ammonia as a carbon-free fuel, and covers recent technological solutions to overcome the barriers with the production, storage and usage of green ammonia. One way to decarbonize the energy industry is by converting electrical energy into chemical energy via water electrolysis to produce hydrogen. Hydrogen can then be stored, used in a fuel cell to generate electricity, or burnt cleanly with air to generate heat, steam, producing only water as a by-product. However, hydrogen has an extremely low density, even when compressed, which means that its energy density on a volumetric basis remains distinctly substandard to most liquid fuels, hydrogen also has a much wider range of concentrations over which it remains potentially explosive. Ammonia alternatively is ~ 18% hydrogen by weight, which means that in terms of hydrogen density, it is ~ 50% higher than compressed or liquefied hydrogen. One major advantage is that there is an existing infrastructure for the production, transport and distribution of ammonia worldwide. Although ammonia in theory can be combusted to produce only nitrogen and water as emissions, in practice, several challenges arise, nitrous oxides (NOx) are often generated, especially if the combustion happens at higher temperatures and/or under pressure, in vehicle engines, gas turbines and as rocket fuel. To overcome such challenges, further research into ammonia combustion phenomena is required. This review sheds light on recent technological advancements with ammonia from the production point to the utilization end point. Moreover, the study concludes with a techno-economic evaluation and global market trends of ammonia in the COVID-19 crises.